Advanced communication games : - Hadfield, Jill (Longman, 1997)
This series offers a collection of communicative games and activities that require students to use the language in order to complete tasks successfully at three levels. Each book in the series features: A collection of 40 reproducible games, Full teaching notes for each game and Pair work, group work, and whole class activities. Activities include information gap, guessing games, search and matching games, quizzes, board games, role play, and simulation.